Analisis Dampak Teknologi Artificial Intelligence Terhadap Manajemen Pemasaran - Sayful Amrin (Ekspektasi: Jurnal Pendidikan Ekonomi, 2025)
This research aims to analyze the impact of Artificial Intelligence (AI) technology on marketing management in the digital era. Using a qualitative approach with descriptive analysis, this research examines the transformation that occurs in marketing practices due to the application of AI technology. The research results show that AI has a significant impact on various aspects of marketing management, including customer segmentation, content personalization, marketing process automation, predictive analysis, and customer experience. Positive impacts identified include increased operational efficiency, targeting accuracy and marketing campaign ROI. However, there are also challenges in the form of the need for large technology investments, dependence on quality data, and customer privacy issues. This research recommends that companies develop a gradual AI implementation strategy, increase HR capabilities, and build a robust data infrastructure to maximize the benefits of AI technology in marketing management.